Identifying producers of antibacterial compounds by screening for antibiotic resistance - Thaker, Maulik N; Wang, Wenliang; Spanogiannopoulos, Peter; Waglechner, Nicholas; King, Andrew M; Medina, Ricardo; Wright, Gerard D (Nature biotechnology, 2013)
Selecting for microorganisms resistant to known antibiotics enables discovery of strains that produce structurally related compounds. Microbially derived natural products are major sources of antibiotics and other medicines, but discovering new antibiotic scaffolds and increasing the chemical diversity of existing ones are formidable challenges. We have designed a screen to exploit the self-protection mechanism of antibiotic producers to enrich microbial libraries for producers of selected antibiotic scaffolds. Using resistance as a discriminating criterion we increased the discovery rate of producers of both glycopeptide and ansamycin antibacterial compounds by several orders of magnitude in comparison with historical hit rates. Applying a phylogeny-based screening filter for biosynthetic genes enabled the binning of producers of distinct scaffolds and resulted in the discovery of a glycopeptide antibacterial compound, pekiskomycin, with an unusual peptide scaffold. This strategy provides a means to readily sample the chemical diversity available in microbes and offers an efficient strategy for rapid discovery of microbial natural products and their associated biosynthetic enzymes.